Krokot (Portulaca oleracea L) As a Natural Sensitizer for TiO2 Dye-sensitized Solar Cells: The Effect of Temperature Extract - Reyza Anni Mufidah; Khamidinal Khamidinal; Endaruji Sedyadi; Didik Krisdiyanto (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2015)
The solar cell is formed by a sandwich structure, in which two electrodes flank the primary electrolyte that is containing redox I-/based on PEG (Polyethylene Glycol). The working-electrode which is TiO2 layer on an ITO glass substrate is sensitized with krokot dye as the electron donor. The counter electrode is a layer of carbon. The fabrication cell is immersed with the krokot dye with 40°C, 50°C, 60°C extract temperature. The result of the UV-Vis shows that the absorption of wave-length from dye extract of krokot is located in the visible region with the absorbance peak in 420,5 nm and 665,5 nm which are the peak of chlorophyll. For the UV-Vis solid system, there are the highest band gap in 50°C extract temperature that make the capability of absorption toward UV spectrum is large. Furthermore, in the functional group analysed by FT-IR, there are shiften-carbonil and hydroxyl group after they are sensitized. From the current and voltage test with I-V meter keithley 2400 is resulted that on the 50°C extract temperature produces the highest efficiency of reaches which is 2.63 x 10-3 %.